In vitro propagation of Vanda tessellata (Roxb.) Hook. ex G. Don from seed-derived protocorms (Botanica Orientalis: Journal of Plant Science, 2020)
Vanda tessellata (Roxb.) Hook. ex G. Don, a monopodial epiphytic orchid, is renowned for its horticultural and medicinal values. This study aims to develop a protocol for its propagation through in vitro grown protocorms. Protocorms were cultured on different strengths of Murashige and Skoog (MS) medium; full, half and quarter, without the addition of any organic additives. Quarter strength of MS medium was found to be effective for the development of shoots and shoot buds earlier than other media tested. Shoot multiplication was carried out in different concentrations of coconut water (CW), gibberellic acid (GA3), 6-benzylaminopurine (BAP) and α-naphthalene acetic acid (NAA) supplemented quarter strength of MS medium with 3% sucrose, and BAP supplemented quarter strength of MS medium with 6% sucrose. Among them, quarter strength of MS medium supplemented with 0.5 mg/l BAP was found to be effective for shoot formation, quarter strength of MS medium with 1.5 mg/l BAP plus 6% sucrose was effective for shoot bud development, and quarter strength of MS medium with 0.5 mg/l NAA was effective for root formation. The higher number of leaves was found on quarter strength of MS medium supplemented with 1.5 mg/l GA3 plus 3% sucrose, whereas longer leaves were found on quarter strength of MS medium supplemented with 0.5 mg/l GA3 and 3% sucrose. The protocol developed in this study can be used for the mass propagation and conservation of V. tessellata.